2007
DOI: 10.1007/s00240-007-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of a clean face: the effect of different washing procedures on the association of Tamm–Horsfall glycoprotein and other urinary proteins with calcium oxalate crystals

Abstract: This study was undertaken to determine whether the use of different washing procedures could explain dissident findings in published studies examining the role of urinary macromolecules in urolithiasis. Calcium oxalate monohydrate (COM) crystals were deposited from or added to the same sieved urine, washed with copious or limited amounts of distilled water, or with methanol, and examined by field emission scanning electron microscopy (FESEM). Demineralized extracts were analysed by SDS-PAGE and Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 53 publications
5
36
0
Order By: Relevance
“…A number of studies (1, 46) used high-resolution SXRD to demonstrate the presence of intracrystalline proteins in biogenic calcite crystals, a method that we have also previously applied to confirm that COM crystals precipitated from human urine contain intracrystalline proteins (17). Using the same technique, we have shown that urinary COM crystals have raised lattice strains and decreased crystallite sizes proportional to the concentration of crystal matrix macromolecules in the urine from which they were generated, thus confirming that proteins are incarcerated within the CaOx mineral bulk and substantiating our previous data demonstrating similar dose-response relationships with increasing concentrations of prothrombin (49). Increased lattice strain and reduced crystallite size result from the presence of intracrystalline defects and discontinuities, which destabilize the crystalline structure and thereby render it more susceptible to proteolytic invasion and dissolution.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…A number of studies (1, 46) used high-resolution SXRD to demonstrate the presence of intracrystalline proteins in biogenic calcite crystals, a method that we have also previously applied to confirm that COM crystals precipitated from human urine contain intracrystalline proteins (17). Using the same technique, we have shown that urinary COM crystals have raised lattice strains and decreased crystallite sizes proportional to the concentration of crystal matrix macromolecules in the urine from which they were generated, thus confirming that proteins are incarcerated within the CaOx mineral bulk and substantiating our previous data demonstrating similar dose-response relationships with increasing concentrations of prothrombin (49). Increased lattice strain and reduced crystallite size result from the presence of intracrystalline defects and discontinuities, which destabilize the crystalline structure and thereby render it more susceptible to proteolytic invasion and dissolution.…”
Section: Discussionsupporting
confidence: 84%
“…The ultrafiltered (10 kDa) sample was divided into five portions, to which CME was added to give final concentrations of 0, 0.5, 1.0, 2.0, and 5.0 mg/l. Radiolabeled and nonradiolabeled urinary COM crystals were then precipitated from each sample (7), filtered (0.22 m), washed (49), lyophilized, and stored at Ϫ70°C. Before use, crystals were sterilized by ethylene oxide and suspended (400 g/ml) in PBS saturated with CaOx, which we have shown in unpublished work does not alter their binding to or internalization by cells, or their vulnerability to proteolytic degradation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations